Penentuan Waktu Optimum Pirolisis Limbah Biomassa Serbuk Gergaji Batang Kelapa Menggunakan Gas Inert Argon - Takdir Syarif; Andi Aladin; Basri Modding; Resky Alqadri Rahmatullah; Nurul Makka Mustafa (Journal of Chemical Process Engineering, 2023)
This study aims to determine the effect of argon inert gas and pyrolysis time variations on the quality of charcoal produced from the pyrolysis of coconut sawdust waste. This research was carried out in a pyrolysis reactor operating at 400 oC, with an inert gas rate of 2 liters/minute with time variations of 60, 90, 120, 150, and 180 minutes. The results of the research obtained products in the form of charcoal and liquid smoke. Pyrolysis using inert gas has a heating value of 7229 kcal/kg. While the treatment without inert gas has a calorific value of 7050 Kcal/kg. This complies with SNI 1683-2021 concerning Wood Charcoal, which is a minimum of 6500 Kcal/kg. The optimum time obtained is 150 minutes with the characteristics of charcoal: (1) the volatile matter of 16.85% wt, (2) moisture of 2.47% wt, (3) ash content of 4.11% wt, and (4) fixed value carbon 76.57%wt.